The stolen gold affair - Pronzini, Bill (Muller, Marcia. Carpenter and Quincannon mystery., 2020)
"Despite the fact that his wedding is right around the corner, John Quincannon takes on what may be his riskiest assignment: going undercover into a gold mine to ferret out a gang hijacking high-grade ore before it reaches the surface ... John discovers the clever methods by which the scheme is being worked and exposes the conspirators ... following him leads to an unexpected rendezvous with Sabina, who has uncovered vital information about the thief's true identity and whereabouts. Working together, they corner their quarry in a wild battle aboard a speeding train."--Provided by Publisher.